THE YOUTUBERS PHENOMENON: WHAT MAKES YOUTUBE STARS SO POPULAR FOR YOUNG PEOPLE? - Sara PEREIRA,Pedro MOURA,Joana FILLOL (Fonseca, Journal of Communication, 2023)
This paper aims to explore and to analyse the channels and the five most viewed videos published in May 2017 by two YouTubers – the Portuguese Wuant and the Swede PewDiePie. These YouTube stars were highlighted by a sample of Portuguese teenagers during the fieldwork of the European research project Transmedia Literacy.